Sprouts - Schwartau, Svitlana (My University, 2014)
Sprouts are the germinated seeds of various herbaceous plants, including vegetables, herbs, and field crops. The entire germinated plant (root, shoot, cotyledons, and remnant seed coat) is sold for use mainly in salads and sandwiches. Sprouting is considered a form of food processing, rather than agricultural crop production.
Keywords: sprouts; germinated plant; plants; рослини; пророслі рослини; паростки; ростки; проросшие растения; растения